Novel NtA and LG1 Mutations in Agrin in a Single Patient Causes Congenital Myasthenic Syndrome - Wang, Aiping; Xiao, Yangyang; Huang, Peng; Liu, Lingjuan; Xiong, Jie; Li, Jian; Mao, Ding'an; Liu, Liqun (Frontiers in Neurology, 2020)
Congenital myasthenic syndrome (CMS) is a group of genetic disorders of neuromuscular transmission that is characterized by muscle weakness. A mutation in the gene encoding agrin (AGRN) is a rare cause of CMS, and only a few families or isolated cases have been reported. We reported a pediatric proband exhibiting muscle weakness in the trunk and limbs with skeletal malformation and intellectual disability and performed whole-exome sequencing of the proband parent-offspring trio. Results revealed a new compound heterozygous mutation in AGRN: c.125A>C (p.Glu42Ala) in the N-terminal agrin domain (NtA) and c.4516G>A (p.Ala1506Thr) in the laminin G1 domain (LG1). Bioinformatic analysis predicted the mutation as possibly pathogenic. The new compound heterozygous mutation in AGRN may disrupt agrin’s known function of bridging laminin and α-dystroglycan and undermine the formation and maintenance of the neuromuscular junction (NMJ) via both muscular and neural agrin pathways. It may also induce secondary peripheral neuropathy and skeletal malformation.